Risk factors for COVID-19-associated mucormycosis (CAM): A case-control study - Akkilagunta Sujiv; N. R. Aiswarya Lakshmi; Pradeep Ramrao Deshmukh; Jaya Prasad Tripathy; Mubashshera F. Khan; Victoria Thomas (Journal of Family Medicine and Primary Care)
Introduction: Mucormycosis, a rare but serious fungal infection, surged during the second wave of the COVID-19 pandemic. Despite various proposed causative factors, published data are limited. This study aimed to identify risk factors for COVID-19-associated mucormycosis. Methods: A case-control study was conducted in the Nagpur district. Cases were recruited from suspected or confirmed mucormycosis cases reported to district health authorities. Controls were household members who had COVID-19 but did not develop mucormycosis. Predisposing and treatment-related factors were analyzed. Results: Analysis revealed significant associations between mucormycosis and diabetes mellitus (OR-10.8; CI-1.1–103.6) and corticosteroid use (OR-97.6; CI-3.2–2927.1). Factors such as humidifier use and mask usage did not show a significant association. Conclusion: Optimal use of oxygen and corticosteroids is crucial, particularly in diabetic COVID-19 patients, to prevent mucormycosis.